THE EFFECT OF THE EXTRACTIVE SPECIES PLACEMENT MODEL ON THE FEED CONVERSION RATIO (FCR) OF TILAPIA IN THE INTEGRATED AGRICULTURE AQUACULTURE (IAA) SYSTEM OF THE GIS-BASED FLOATING-BED MODEL - Ulfiani Ulfiani; Nursyahran Nursyahran; Heriansah Heriansah; Fathuddin Fathuddin; Arnold Kabangnga (Journal of Fisheries and Marine Resource Management, 2026)
The two main sectors, agriculture and fisheries, play an important role in ensuring food security and community nutrition. However, limited land, water resources, and energy are problems that these two sectors often face. Research on FCR on a GIS-based floating-bed model IAA system can provide important information on how to improve the efficiency and productivity of the system. This study aims to determine the effect of the extractive species placement model on the Feed Conversion Ratio (FCR) of tilapia (Oreochromis niloticus) in the Integrated Agriculture Aquaculture (IAA) system of the GIS-based floating-bed model. The study used a Complete Random Design (RAL) with three treatments and three replicates. The treatments tested were Treatment A (no floating-bed transfer during maintenance), Treatment B (10-day interval transfer), and Treatment C (20-day interval transfer). The research was carried out for 90 days in the pool of the People's Hatchery Unit (UPR) Sipurennu, Citta District, Soppeng Regency. The main parameter observed is the FCR value. The results showed that the FCR values in Treatment A, B, and C were 1.03, 1.09, and 1.08, respectively. ANOVA analysis showed no significant difference between treatments (F=0.389, Sig.=0.694). The conclusions of the study showed that the effect of the extractive species placement model on the Feed Conversion Ratio (FCR) of tilapia (Oreochromis niloticus) in the Integrated Agriculture Aquaculture (IAA) system of the GIS-based floating-bed model effectively resulted in a low FCR value in the range of 1.03-1.09, with the lowest value at treatment A (without floating-bed transfer during maintenance).